Crescimento inicial de Physalis peruviana L. em diferentes substratos - Hansen, Edson Francisco (2016)
The objective of this work was to evaluate the initial growth of Physalis peruviana in different substrates. The treatments used were T1: the commercial substrate as a control (100%); T2: forest soil (100%); T3: forest soil (50%) + sawdust (50%); T4: forest soil (50%) + cattle manure (50%); And T5: forest soil (50%) + aviary bed. A randomized block design with five treatments and four replications was used. After 45 and 60 days of sowing date, the following variables were analyzed: seedling height, stem diameter and leaf area. The data were submitted to analysis of variance and to the test of tukey to 5%. It was concluded that the treatment with forest soil + bed of aviary provides better conditions for Physalis peruviana seedlings production.